The effectiveness of the product-based learning model corresponding to Indonesian national standard competency (SKKNI) for the furniture industry in learning applications of wood construction - R.A, Ari Syaiful; Prima, Fani Keprila; Gusmareta, Yuwalitas; Yudistira, Sukma (Universitas Negeri Padang, 2022)
The industrial revolution era has significantly impacted Indonesian education's development. Education is not only monotonous to study students but also provides opportunities to develop themselves according to their interests and talents. In this lecture, students' practicum products usually only become waste and are not yet suitable for use and even worth selling. The researcher plans to develop a Wood Construction Application learning with a product-based learning approach combined with SKKNI no. 61 of 2021, the wood furniture industry standard. This research is essential to find the most suitable strategy or practice in the Wood Construction Applications lecture. This study aims to develop learning based on the wood furniture industry with a product-based learning approach. The type of research used is research and development with the ADDIE model. The targeted outputs are in the form of books. The experimental and control classes' results of the pretest and post-test obtained an average result of pretest 20 and post-test of 93.31. In the control class, the average results of the pretest were 22.5, and the post-test was 73.38. While the results of the N-Gain value in the experimental and control classes, the experimental class obtained a value of 0.92 with a high category. In the control class, a score of 0.65 is included in the medium category.